2022
DOI: 10.5650/jos.ess22207
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizer-free Vitamin E Nanovehicle for Biological Research

Abstract: IntroductionThe natural vitamin E (VE) compounds tocopherol (Toc) and tocotrienol (Tocotri) share common structures with a chromanol head and a phytyl tail. Both compounds interfere with one or more propagation steps of the lipid peroxidation process, which is crucial in therapies of oxidation-induced diseases 1−9) , and therefore the intake from the diet is greatly recommended. However, as natural VE is a lipidsoluble antioxidant, it is lowly soluble in water. To overcome the low affinity in water media, VE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…On the other hand, it is reported that the surfactant-free Toc nanoemulsion with fluid Toc phase exhibited the comparable antioxidant performance to that of Trolox and the corresponding Toc in micelle phases in terms of ABTS radical scavenging performance (Fig. 6b) 77) . Both the diffusion of radical species in the Toc phase and the functional Toc-water interfaces were considered to own the excellent radical scavenging performance.…”
Section: Ves As Antioxidant In Food Systemsmentioning
confidence: 89%
“…On the other hand, it is reported that the surfactant-free Toc nanoemulsion with fluid Toc phase exhibited the comparable antioxidant performance to that of Trolox and the corresponding Toc in micelle phases in terms of ABTS radical scavenging performance (Fig. 6b) 77) . Both the diffusion of radical species in the Toc phase and the functional Toc-water interfaces were considered to own the excellent radical scavenging performance.…”
Section: Ves As Antioxidant In Food Systemsmentioning
confidence: 89%
“…Notably, Toc readily exhibits high dispersibility in the absence of CDs or surface-active species such as surfactants and exhibited excellent ABTS radical scavenging effects, even in the dispersion state comparable to watersoluble Trolox and 2,2,5,7,8-pentamethyl-6-chromanol (PMC) 69) . Furthermore, the study on the basic thermal behavior of pure ascorbic acid 6-palmitate (ASP) , a representative lipophilic vitamin C derivative, confirmed the formation of the intermediated state consisting of Cr and LC phases after cooling of the LC state obtained by heating only above T m .…”
Section: Vitamin E Complex With Various Cds In the Absence Of Organic...mentioning
confidence: 99%